Remodelista : the low-impact home : a sourcebook for stylish, eco-conscious living - Guralnick, Margot; Winston, Fan (Artisan, 2022)
"Low-impact living is about making thoughtful, eco-friendly choices in your home. But being sustainable doesn't have to mean sacrificing style. That's where Remodelista comes in. In this comprehensive guide, they decode the secrets to creating a home that's good for the planet-and totally livable"--